Customer relationship management strategies in small and medium enterprises: a study in tourism industry in Vietnam / Vu Minh Ngo, Hieu Minh Vu and Mai Hong Nguyen - Vu, Minh Ngo; Hieu, Minh Vu; Mai, Hong Nguyen (Universiti Teknologi MARA, Shah Alam: Accounting Research Institute (ARI), 2020)
Small and Medium Enterprises (SMEs) are one of the main motors for economic growth, especially in developing countries like Vietnam. However, SMEs are usually overlooked in academic research especially on the topic of competitive advantage of firms. Recently, Customer Relationship Management (CRM) has become a prominent tool in the business for building long term competitive advantage. The primary purpose of this study was to analyze CRM strategies that are currently being implemented in SMEs and identify determinants of successful CRM implementation in SMEs. Adopting grounded theory research procedures, this study investigated the practices of CRM executions in 41 SMEs in Vietnam's tourism sector. This study provides novel insights and guidelines for managers and supports them in choosing and implementing CRM practices for building long-term competitive advantages in SMEs.